MATERIAL WITNESS. - JONES, KATE (Times Higher Education)
The article focuses on topology optimisation studies led by Professor Mike Xie at RMIT University's Centre for Innovative Structures and Materials (CISM), including the well known study on the Evolutionary Structural Optmisation method and the Bi-directional Evolutionary Structural Optimisation method. Topics discussed include benefits of using materials with new or unusual properties and his collaboration with other researchers on coming up with biomimetic and biocompatible bone implants.